Utilization of Digital Marketing to Increase Sales Volume and the Economy of Communities Around Oyster Mushroom Processing Production in Tulungagung Regency - Prabowo, Kus Irawan (Jurnal Ilmiah Ekotrans & Erudisi, 2023)
The objective of the present study was to ascertain a resolution and establish a correlation pertaining to the application of digital marketing in enhancing the volume of product sales and the economic well-being of the local community engaged in the production of oyster mushroom processing within Tulungagung Regency. Additionally, this study aimed to identify the challenges or issues encountered by entrepreneurs in leveraging digital marketing, thereby facilitating the effective and efficient implementation of strategic initiatives. The research methodology employed in this investigation is descriptive in nature, utilizing a qualitative approach. The data type utilized comprises primary data obtained through structured interviews and direct observations. The findings from the discussion indicate that the utilization and activities associated with digital marketing yield highly favorable and beneficial effects on product sales volume and contribute positively to the economic development of the community involved in the oyster mushroom processing sector in Tulungagung Regency. The digital marketing strategies employed encompass the deployment of internet media, various digital platforms (including WhatsApp, Shopee, TikTok, and Tokopedia), and the creation of innovative video content, which collectively enhance brand visibility, expand marketing reach, and attract new clientele. Nevertheless, it is imperative that entrepreneurs engaged in oyster mushroom processing within Tulungagung Regency promptly address several challenges encountered in practice, notably including the requisite skills and competencies for effectively utilizing the internet and digital platforms, as well as constraints relating to human resources and the availability of stable and continuous raw materials.